OPTIMALISASI PENDIDIKAN AL-QUR’AN DALAM PENGEMBANGAN PENDIDIKAN AGAMA ISLAM - ., Rosmiyati; Abubakar, Achmad; Abunawas, Kamaluddin; Masâ€™ud , Mukhtar (Inspiratif Pendidikan, 2022)
The basis for implementation Al-Qur’an education includes Government policies, financing, namely funding sources, education management functions in the implementation of Al-Qur’an education, utilization of human resources, and members as well as students. Implementation challenges of Al-Qur’an education, among others: the era of globalization, human moral decadence, and prioritizing world affairs that can provide something material and less inclined to pursue amaliyah for preparation and provision in the hereafter. Expectations in the implementation of Al-Qur’an education, among others: building believers and increasing intelligence in the field of religion, increasing friendship and Ukhuwah Islamiyah relations, and centers of knowledge in society, namely the implementation of Al-Qur’an education provides great hope for Muslims, namely the information center for the development of Islamic knowledge, the center for fostering Islamic knowledge, and the Islamic religious consultation center.